Basic elements of rules of metrics in arabic prosody for Nigerian students (2015)
While prosody has been one of the linguistic subjects in various Arabic schools, its study has been equally characterized by precarious situation ranging from the methods by the teachers particularly in the local madrasa. This half-baked knowledge has been the basis of the subject up to the University level which constitutes a serious problem of background to the subject. This paper wishes to correct the situation by examining the problems and attempts to simplify the method that could be adopted during the process of alteration and addition in Arabic Prosody with simple and familiar illustration to West Africa Arabic students with particular reference to Nigeria.